On Dove Cottage - Cowton, Jeff (Romanticism on the Net, 2023)
At age fourteen, Thomas De Quincey (1785–1859) read a manuscript of a Wordsworth poem from Lyrical Ballads and his life was transformed. Eight years later he visited Wordsworth’s Grasmere home of Dove Cottage, becoming its tenant two years after that. In the years there which followed, De Quincey developed a strong addiction to opium and wrote of his experiences in Confessions of an English Opium Easter, a best-selling book published in 1822. This video discusses the background to this work, featuring the author’s opium scales and manuscript.